Using Item Response Theory for the Development of a New Short Form of the Eysenck Personality Questionnaire-Revised - Colledani, Daiana; Anselmi, Pasquale; Robusto, Egidio (Frontiers in Psychology, 2018)
The present work aims at developing a new version of the short form of the Eysenck Personality Questionnaire-Revised, which includes Psychoticism, Extraversion, Neuroticism, and Lie scales (48 items, 12 per scale). The work consists of two studies. In the first one, an item response theory model was estimated on the responses of 590 individuals to the full-length version of the questionnaire (100 items). The analyses allowed the selection of 48 items well discriminating and distributed along the latent continuum of each trait, and without misfit and differential item functioning. In the second study, the functioning of the new form of the questionnaire was evaluated in a different sample of 300 individuals. Results of the two studies show that reliability of the four scales is better than, or equal to that of the original forms. The new version outperforms the original one in approximating scores of the full-length questionnaire. Moreover, convergent validity coefficients and relations with clinical constructs were consistent with literature.